ANALISIS PERBANDINGAN KUALITAS DAN BIAYA PENGGUNAAN MECHANICAL COUPLER PADA KONSTRUKSI PIER PROYEK MRT JAKARTA CP 103 - Pungky Dharma Saputra (Politeknik Negeri Jakarta, 2020)
The Government of Indonesia is accelerating the development of railway infrastructures. MRT is a milestone in the development of railway infrastructures in Indonesia since 2013. The elevated construction uses a single pier structure with a main reinforcement bar diameter of 40 mm. However, the conventional overlapping connection is unsuitable; hence it used a mechanical coupler connection. This research focused on the quality and cost comparison of using a mechanical coupler as a reinforcing connection in the MRT CP 103 Project's pier construction. The variables which would be studied were conventional connection and mechanical coupler connection. There were two stages in this research: quality testing in an independent laboratory and a cost comparison analysis. The data used were primary data from quality testing results, and secondary data were the project volume and unit price. The project sample in this research was MRT CP 103 Project with Pier AP 29 as the case study. The analytical approach used was descriptive analysis by making a comparison of the two variables. According to the quality test results, the tensile strength of the reinforcement was 665.56 N/mm2 and the mechanical coupler tensile strength was 626.33 N/mm2 . According to the calculation results of the case study on Pier AP29, it was found that the price difference was IDR2,246,622 or 6.17% cheaper than conventional connection. Further analysis showed that the mechanical coupler connection with 40 mm diameter was very effective because it was cheap. This research can be used as a reference in the alternative selection of reinforcement connection. Keywords : Quality, Cost, Mechanical Coupler, Pier, MRT CP 103 Project.